Profesionalisme Guru dalam Mengembangkan Kurikulum Merdeka pada Pembelajaran PAI di SDN 006 Buahbatu Kota Bandung - Neneng; Rohanih; Rosidah Rahman; Ulfah (Tarbiatuna: Journal of Islamic Education Studies, 2025)
Teacher professionalism is a key factor in improving the quality of education in Indonesia, contributing significantly to the overall progress of national education. This study aims to analyze the role of professional teachers in the development of the Independent Curriculum in Islamic Religious Education (PAI) learning at SDN 006 Buahbatu. This study used a qualitative approach with descriptive analysis methods. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that teachers at SDN 006 Buahbatu have implemented the principles of the Independent Curriculum, including in developing appropriate teaching materials that are tailored to the context and needs of students. Teachers are also active in creating an inclusive and supportive learning environment and implementing various innovative learning methods to increase student participation. From the results of the study, it can be concluded that teacher professionalism has an impact on the success of the Independent Curriculum development in PAI learning.